Pengaruh Merk Filamen Pla Terhadap Kuat Tarik Spesimen Uji Astm D638 Type V - Rafiq Muhammad, Naufal; Hasdiansah, Hasdiansah; Sugianto, Sugianto (Jurnal Inovasi Teknologi Terapan, 2023)
3D printing is Additive Manufacture which is and additive manufacturing. Since it was discovered and developed in 1981, the presence of 3D printing has transformed into an important element of manufacturing technology. Starting from printing spare parts and even making houses in this era, the role of 3D printing cannot be separated. This study aimed to determine the effect of various brands of polylactic acid (PLA) type filaments on the tensile strength test. The Taguchi method with the Orthogonal Array L_27 3^13 experimental design with 5 factors is the method used in this study. obtained by the tensile test parameters with the highest effect on the layer thickness of 0.15, M filament, print speed of 55 mm/s, then the nozzle temperature of 230˚C, and finally the Z orientation of 40˚. It was observed that nozzle tempe Nozzle temperature, print speed, and z orientation were observed to havethe layer thickness and the choice of filament significantly affect the tensile test strength.